Acute Ethanol Challenge Differentially Regulates Expression of Growth Factors and miRNA Expression Profile of Whole Tissue of the Dorsal Hippocampus - Barney, Thaddeus M.; Vore, Andrew S.; Deak, Terrence (Frontiers in Neuroscience, 2022)
Acute ethanol exposure produces rapid alterations in neuroimmune gene expression that are both time- and cytokine-dependent. Interestingly, adolescent rats, who often consume binge-like quantities of alcohol, displayed reduced neuroimmune responses to acute ethanol challenge. However, it is not known whether growth factors, a related group of signaling factors, respond to ethanol similarly in adults and adolescents. Therefore, Experiment 1 aimed to assess the growth factor response to ethanol in both adolescents and adults. To test this, adolescent (P29–P34) and adult (P70–P80) Sprague Dawley rats of both sexes were injected with either ethanol (3.5 g/kg) or saline, and brains were harvested 3 h post-injection for assessment of growth factor, cytokine, or miRNA expression. As expected, acute ethanol challenge significantly increased IL-6 and IκBα expression in the hippocampus and amygdala, replicating our prior findings. Acute ethanol significantly decreased BDNF and increased FGF2 regardless of age condition. PDGF was unresponsive to ethanol, but showed heightened expression among adolescent males. Because recent work has focused on the PDE4 inhibitor ibudilast for treatment in alcohol use disorder, Experiment 2 tested whether ibudilast would alter ethanol-evoked gene expression changes in cytokines and growth factors in the CNS. Ibudilast (9.0 mg/kg s.c.) administration 1 h prior to ethanol had no effect on ethanol-induced changes in cytokine or growth factor changes in the hippocampus or amygdala. To further explore molecular alterations evoked by acute ethanol challenge in the adult rat hippocampus, Experiment 3 tested whether acute ethanol would change the miRNA expression profile of the dorsal hippocampus using RNASeq, which revealed a rapid suppression of 12 miRNA species 3 h after acute ethanol challenge. Of the miRNA affected by ethanol, the majority were related to inflammation or cell survival and proliferation factors, including FGF2, MAPK, NFκB, and VEGF. Overall, these findings suggest that ethanol-induced, rapid alterations in neuroimmune gene expression were (i) muted among adolescents; (ii) independent of PDE4 signaling; and (iii) accompanied by changes in several growth factors (increased FGF2, decreased BDNF). In addition, ethanol decreased expression of multiple miRNA species, suggesting a dynamic molecular profile of changes in the hippocampus within a few short hours after acute ethanol challenge. Together, these findings may provide important insight into the molecular consequences of heavy drinking in humans.